Relationship between periodontitis and systemic diseases: Leptin, a new biomarker? - Hansa Jain; Sanjyot Mulay (Wolters Kluwer Medknow Publications, 2014)
Background: Leptin is a polypeptide hormone associated with the occurrence of legion of diseases including obesity, cardiovascular diseases, and diabetes. Periodontitis, that is, inflammation of the periodontium has also been linked to a number of systemic manifestations. Aim: The aim of the present study was to analyze the role of leptin as a biomarker linking periodontitis with obesity, cardiovascular diseases, and diabetes. Setting and Design: The inclusion criteria included, clinical trials available in English language; studies involving human participants; studies relating leptin and periodontal diseases to either obesity, cardiovascular diseases or diabetes. Exclusion criteria enlisted manuscripts in language other than English; if they were case reports, narrative reviews, personal communication, conference presentations, editorial and expert opinion; experiments not involving humans. Methods: We performed a literature search encompassing the time period from January 2000 to May 2013. A systematic search of the Cochrane Library and the Medline through PubMed was performed using the selected keywords/phrases "leptin and periodontitis," "leptin and periodontal diseases," "leptin, periodontitis and obesity," "leptin, periodontitis and cardiovascular diseases," and "leptin, periodontitis, and diabetes." Result: A total of 23 studies was obtained using the selected keywords/phrases. On screening, the chosen studies seven fulfilled the inclusion criteria. Four demonstrated association of leptin with periodontitis and obesity. One study associated cardiovascular diseases and periodontitis through leptin whereas two were found linking leptin, periodontitis, and diabetes mellitus. Conclusion: We could find some positive consociation between the serum concentration of leptin, periodontitis, and systemic diseases including obesity and cardiovascular diseases. The results were conflicting when its relation with diabetes mellitus type 2 was examined, as one study favored the association whereas the other one claimed that there was no effect on the levels of leptin.